Robot-Assisted Infratrigonal Vesicovaginal Fistula Repair - João Pádua Manzano; Fábio da Silva Crochik; Felipe Guimarães Pugliesi; Renato Vasconcelos Souza de Almeida; Petronio Augusto de Souza Melo; Ricardo Luís Vita Nunes (Case Reports in Urology)
Background. Although relatively rare, vesicovaginal fistula is the most common genitourinary fistula, causing a significant decrease in patients’ quality of life. Location of fistula is major supratrigonal, with some cases located in the trigone and rarely below it. Disease treatment is surgical, and repair can be performed by several techniques, including robot-assisted. Case Presentation. We present a case of a patient who developed an infratrigonal vesicovaginal fistula after treatment of a cervical cancer. The patient was submitted to robotic repair of the vesicovaginal fistula. Conclusion. The use of robot-assisted laparoscopy is expanding over all areas of urology and its applicability to repair vesicovaginal fistulas brings good results.